Aspect-Oriented Fault Injection for the Non-Intrusive Resilience Evaluation of Cryptographic Hardware Models - Mestiri, Hassen; Bouraoui, Mariem; Machhout, Mohsen (Engineering, Technology & Applied Science Research, 2026)
Evaluating the resilience of sophisticated cryptographic hardware against fault injection attacks necessitates high-speed simulation environments. At the Electronic System Level (ESL), SystemC provides a valuable framework for constructing fast functional models. However, traditional fault injection techniques require direct and intrusive code modifications to these models, which complicates the security assessment process. This paper proposes a novel methodology that circumvents this limitation by leveraging Aspect-Oriented Programming (AOP). A non-intrusive fault injection and detection environment is introduced, where faults are woven into SystemC cryptographic models using AspectC++, eliminating the need for source code alterations and offering a practical alternative to complex physical cryptanalysis. This approach is validated through a thorough case study on a SystemC model of the LED lightweight algorithm, focusing on two critical aspects: the efficacy of AOP for accurate fault detection and its overhead regarding simulation performance and executable size. The results demonstrate that the proposed method effectively evaluates a design's efficiency against fault attacks. It is also confirmed that AOP integration imposes a negligible impact on simulation time, preserving the speed advantages of ESL simulation while enabling seamless security analysis.